Refractory multiple brain abscesses caused by Prevotella loescheii and Porphyromonas gingivalis: successful endoscopic lavage and drainage: a case report and review of the literature - Dai, Lirui; Zhan, Wenyi; Huang, Xinyuejia; Lyu, Liang; Jiang, Shu; Zhou, Peizhi (Frontiers in Medicine, 2026)
BackgroundBrain abscesses represent life-threatening conditions, with management complexities significantly heightened in cases involving multiple lesions that are refractory to standard empirical therapies. Prevotella loescheii and Porphyromonas gingivalis, anaerobic bacteria typically residing within the oral flora, are infrequent yet formidable pathogens responsible for intracranial abscess formation. The fastidious nature of these microorganisms often results in delayed diagnosis and initiation of targeted treatment.Case presentationA 25-years-old male presented with a 1-month history of cough, sputum production, and persistent high-grade fever reaching 41 °C. Initially diagnosed with a brain abscess at a local hospital, he received empirical treatment with ceftriaxone, acyclovir, and mannitol, which failed to yield clinical improvement. His condition subsequently deteriorated, characterized by disturbances in consciousness and dysarthria. The antimicrobial regimen was escalated to include vancomycin and meropenem. Despite these efforts, the patient’s neurological status continued to decline, with imaging studies revealing the development of multiple new intracranial abscesses and diffuse intracranial hypertension. Surgical intervention was undertaken, involving abscess excision and decompressive craniectomy. Postoperative imaging 1 week later showed further abscess expansion and the onset of right-sided hemiplegia. Upon admission to our institution, metagenomic next-generation sequencing (mNGS) of the cerebrospinal fluid identified the presence of Prevotella loescheii and Porphyromonas gingivalis. The antimicrobial regimen consisting of vancomycin and meropenem was maintained, and the patient underwent endoscopic intracranial abscess lavage with burr hole external drainage. This integrated approach led to significant radiographic resolution of the abscesses and a gradual improvement in the patient’s level of consciousness. The refractory infection was traced back to an oropharyngeal source.ConclusionThis case highlights the critical diagnostic value of mNGS in detecting fastidious oral anaerobic pathogens in culture-negative refractory brain abscesses. It illustrates that a combination of targeted antibiotic therapy and minimally invasive surgical intervention–specifically, endoscopic lavage and drainage–can be highly effective in managing complex, multi-loculated abscesses caused by Prevotella loescheii and Porphyromonas gingivalis. Maintaining a high index of suspicion for an odontogenic or oropharyngeal origin is crucial in the diagnostic evaluation of such infections.